Justice and Human Rights: A Study of Legal Protection for Victims of Fabricated Arrests in Narcotics Cases - Anan, Moh. Shofi; Maman Suherman, Ade; Setiady, Tri (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
Ideally, the legal system in Indonesia should guarantee justice and uphold human rights by protecting individuals from arbitrary arrests and fabricated cases. However, in reality, incidents of fabricated arrests, particularly in drug-related cases, continue to occur due to weak law enforcement and deficiencies within the system. This study aims to analyze the legal protection mechanisms for victims of fabricated arrests in drug cases from a human rights perspective, with the goal of achieving substantive justice. The methodology used is juridical-normative with a descriptive-analytical approach, utilizing primary and secondary data from literature review and analysis of relevant legal frameworks. The research findings indicate that although regulations exist that provide access to pretrial, compensation, and rehabilitation, their implementation is hindered by complicated procedures and lack of oversight over law enforcement authorities. The human rights perspective emphasizes the importance of physical, psychological, and social recovery for victims as part of efforts to achieve substantive justice.